Comment on ‘Enhancement of carrier mobility in MEH-PPV film prepared under presence of electric field’ by Quanmin Shi [Chem. Phys. Lett. 425 (2006) 353] - Lim, Thong Leng; Chang, C.W.; Inigo, Anto Regis; Huang, Y.F.; White, Jonathon David; Fann, Wunshain (ELSEVIER SCIENCE BV, 2006)
Increased mobility in drop-cast films of MEH-PPV is obtained, when drop cast in the presence of an static electric field. We suggest that this increase is a result of a reduction of nano-domains. (c) 2006 Elsevier B.V. All rights reserved.